2022
DOI: 10.5194/acp-22-8117-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Distinct size dependence and diurnal variation in organic aerosol hygroscopicity, volatility, and cloud condensation nuclei activity at a rural site in the Pearl River Delta (PRD) region, China

Abstract: Abstract. Organic aerosol (OA) has a significant contribution to cloud formation and hence climate change. However, high uncertainties still exist in its impact on global climate, owing to the varying physical properties affected by the complex formation and aging processes. In this study, the hygroscopicity, volatility, cloud condensation nuclei (CCN) activity, and chemical composition of particles were measured using a series of online instruments at a rural site in the Pearl River Delta (PRD) region of Chin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…The κ for organics (κ org ) is assumed to be 0.12. Only the size-resolved κ chem when the particle size >60 nm was calculated because HR-ToF-AMS measurements under 60 nm are considered unreliable . Since the organic mass fraction varies little with particle size for particles larger than 60 nm in this field campaign (Figure S4), the size dependence of the composition should have a small impact on κ chem .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The κ for organics (κ org ) is assumed to be 0.12. Only the size-resolved κ chem when the particle size >60 nm was calculated because HR-ToF-AMS measurements under 60 nm are considered unreliable . Since the organic mass fraction varies little with particle size for particles larger than 60 nm in this field campaign (Figure S4), the size dependence of the composition should have a small impact on κ chem .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…aerosol mass spectrometer and condensation particle counter) was widely used in the estimation of OA volatility (Philippin et al, 2004;Lee et al, 2010). Cai et al (2022) found that the OA volatility was higher at a particle size range of 30 to 200 nm during daytime, suggesting that the SOA formation through gas-particle partitioning could generally occur at all particle sizes. However, this method failed to provide the volatility information of different molecules of OA.…”
Section: Introductionmentioning
confidence: 96%
“…The CCN activity closure analysis, based on the above two methods, is a key means of investigating the impacts of aerosol properties on activation processes. Although CCN measurements were conducted under different environments in the North China Plain, only a few studies established a linkage between CCN activity and chemical composition with a high time resolution [27,[29][30][31]. Additionally, due to the Clean Air Action of the Chinese government initiated in 2013, stringent emission controls have been imposed to decrease fine particulate matter pollution (PM 2.5 , particles smaller than 2.5 µm in diameter) [32].…”
Section: Introductionmentioning
confidence: 99%